Penerapan Pendekatan Andragogi Dalam Pembelajaran Membaca Al-Qur’an Metode UMMI Kelas Dewasa di Madrasah Diniyah Al-Furqan Jember - Mawaddati, Ika Romika; Dahlan, Mukhtar Zaini (Education Journal : Journal Educational Research and Development, 2024)
This paper aims to find out how the andragogical approach is applied in learning to read the Qur’an with the Ummi method for adults at Madrasah Diniyah Al-Furqan Jember. Using a descriptive qualitative approach to the type of field study, with Miles & Huberman technical data analysis. The findings in this study explain that learning the Qur'an with the Ummi method for adults at Madin Al-Furqan applies an andragogical approach, with classroom management according to the 7 stages formulated by the Ummi Foundation; opening, apperception, instilling concepts, understanding concepts, skills, evaluation and closing. The application of the andragogical approach is found in several ways; 1. In determining the study group, it begins with the placement test, to determine the learning readiness of students. 2. The ratio of teachers and students is not always 1: 15, but is adjusted to the age and abilities of students. 3 at the apperception stage, more flexible to increase memorization. 4 Giving an offer to take the munaqosah or final exam. 5 various learning classes are provided. Andragogy approach to create a more fun and humanist learning for adults.